Do physicians lead healthier lifestyles than when they were students? - Tomasz S. Klocek; Przemysław Witek; Patryk Wawrzonkowski; Aleksandra Binek; Nadia Woźniak; Łukasz Krzych (Śląski Uniwersytet Medyczny w Katowicach, 2023)
INTRODUCTION: Lifestyle is a major determinant of health, but this can change over time. Students tend to have worse health behaviors than adults. This interesting phenomenon has not been verified in relation to the medical community. The aim of this study was to evaluate the lifestyle of physicians and compare it with their habits from their student years. MATERIAL AND METHODS: A cross-sectional study was conducted in 2020 using an original questionnaire assessing various lifestyle elements that were classified as "healthy" or "unhealthy" based on World Health Organization recommendations. 112 physicians (64.3% male and 35.7% female) with a median age of 37 years (IQR 36-38) participated in the study. The results were compared with data obtained in this group from the same questionnaire distributed between 2003 and 2005, i.e. when the subjects were medical students. RESULTS: Significant favorable changes were observed regarding less frequent consumption of meals with a high content of table salt (p < 0.01) and increased consumption of fruits and vegetables (p < 0.01). An increased frequency of coffee drinking was observed (p < 0.01). Their dietary habits and stimulant use remained unchanged. There were no differences in physical activity, the occurrence of stress or its nature (mobilizing or destabilizing). CONCLUSIONS: The lifestyles of physicians do not change significantly compared to their student years, which may be related to the habits from their youth.